2021
DOI: 10.1016/j.jviromet.2021.114197
|View full text |Cite
|
Sign up to set email alerts
|

How to choose the right real-time RT-PCR primer sets for the SARS-CoV-2 genome detection?

Abstract: Objectives The SARS-CoV-2 pandemic has created an unprecedented need for rapid large-scale diagnostic testing to prompt clinical and public health interventions. Currently, several quantitative reverse-transcription polymerase chain reaction (RT-qPCR) assays recommended by the World Health Organization are being used by clinical and public health laboratories and typically target regions of the RNA-dependent RNA polymerase (RdRp), envelope (E) and nucleocapsid (N) coding region. However, it is cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…As SARS-CoV-2 continues to spread throughout the globe and within communities, random nucleotide variations in both coding and non-coding areas of the viral genome are under continuous observation 31 . The assays are detecting genetic changes within the spike region which harbors higher variation compared to the relatively conserved N, E, RdRp and ORF1ab genes which most of the conventional RT-qPCR assays detects 32 . Normally, when designing RT-qPCR assays for the detection of SARS-CoV-2, primers should be placed in those regions with the least sequence variation and best conditions for PCR amplification 33 .…”
Section: Discussionmentioning
confidence: 99%
“…As SARS-CoV-2 continues to spread throughout the globe and within communities, random nucleotide variations in both coding and non-coding areas of the viral genome are under continuous observation 31 . The assays are detecting genetic changes within the spike region which harbors higher variation compared to the relatively conserved N, E, RdRp and ORF1ab genes which most of the conventional RT-qPCR assays detects 32 . Normally, when designing RT-qPCR assays for the detection of SARS-CoV-2, primers should be placed in those regions with the least sequence variation and best conditions for PCR amplification 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of sequence conservation between SARS-CoV-2 and MERS-CoV as well as other seasonal human coronaviruses such as HKU1, OC43, NL63 and 229E is important for the establishment of RT-PCR primers and probes. Anantharajah et al, reported that no significant homologies were found between these organisms, suggesting a low risk of false positives during the RT-qPCR diagnosis [ 51 ]. Our study confirms such findings as the number of shared kmers between SARS-CoV-2 and SARS coronavirus HSR 1, MERS-CoV and the human coronavirus HKU1, OC43, NL63 and 229E is 1628, 1, 18, 8, 0 and 18, respectively out of 29,884, i.e., 5% of the total kmers in the case of SARS coronavirus HSR 1, the most similar virus to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Low viral load could hinder proper pathogen identification. Moreover, a study showed that 40–60% of positive SARS-CoV-2 clinical samples are not detected when they exhibit Ct values lower than 30 [ 51 ]. Additionally, a systematic study quantitatively investigated the effect of different mismatches at the 3′-end region of real-time PCR primers.…”
Section: Discussionmentioning
confidence: 99%
“…Two groups of primer-probe sets (Charité/Berlin and CDC designed Primer probe sets) which are recognized globally and used in many diagnostic assays was primarily chosen to be evaluated. Evaluation of these primer probes to find an optimum combination was conducted by thoroughly reviewing the literature [ 25 , 26 , 27 , 28 , 29 , 30 ]. WHO recommended the Charité/Berlin assay which detects two viral targets E and RdRp gene [ 16 ].…”
Section: Discussionmentioning
confidence: 99%